2019
DOI: 10.1038/s41598-019-47616-4
|View full text |Cite
|
Sign up to set email alerts
|

Direct test of the FLRW metric from strongly lensed gravitational wave observations

Abstract: The assumptions of large-scale homogeneity and isotropy underly the familiar Friedmann-Lemaître-Robertson-Walker (FLRW) metric that appears to be an accurate description of our Universe. In this paper, we propose a new strategy of testing the validity of the FLRW metric, based on the galactic-scale lensing systems where strongly lensed gravitational waves and their electromagnetic counterparts can be simultaneously detected. Each strong lensing system creates opportunity to infer the curvature parameter of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 88 publications
(61 citation statements)
references
References 68 publications
2
55
0
Order By: Relevance
“…One example of such an avenue is gravitationally lensed GWs, the first of which may be possible to observe in the next few years (Ng et al 2018;Li et al 2018;Oguri 2018). It has been suggested that lensed GWs might offer interesting applications in fundamental physics, astrophysics, and cosmology (Sereno et al 2011;Liao et al 2017;Collett & Bacon 2017;Fan et al 2017;Baker & Trodden 2017;Lai et al 2018;Dai et al 2018;Mukherjee et al 2019;Oguri 2019;Pang et al 2020;Jung & Shin 2019;Cao et al 2019;Hou et al 2020;Sun & Fan 2019;Hannuksela et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…One example of such an avenue is gravitationally lensed GWs, the first of which may be possible to observe in the next few years (Ng et al 2018;Li et al 2018;Oguri 2018). It has been suggested that lensed GWs might offer interesting applications in fundamental physics, astrophysics, and cosmology (Sereno et al 2011;Liao et al 2017;Collett & Bacon 2017;Fan et al 2017;Baker & Trodden 2017;Lai et al 2018;Dai et al 2018;Mukherjee et al 2019;Oguri 2019;Pang et al 2020;Jung & Shin 2019;Cao et al 2019;Hou et al 2020;Sun & Fan 2019;Hannuksela et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Binary black hole localization combined with an EM redshift measurement could open several new scientific frontiers. The Hubble constant and cosmological inference using lensed gravitational waves has been discussed in previous works in the context of events accompanied by an EM counterpart Liao et al (2017); Cao et al (2019). We have H 0 measurements in the more common scenario of a quadruply imaged binary black hole without an EM counterpart.…”
Section: Discussionmentioning
confidence: 94%
“…More importantly, besides the configuration of multiple signals that could be used to derive cosmological distances [494][495][496], the time difference (Δt i, j ) in the arrival times of two signals (at angular coordinates θ i and θ j on the sky) can also be measured with unprecedented accuracy [469], which are not affected by GW damping effect and DM viscosity. Such advantage of strongly lensed GW signals has been widely discussed concerning fundamental physics [468], cosmology [497], and dark matter [498]. In this analysis, the measured time-delay distance (eq.…”
Section: -13mentioning
confidence: 99%
“…The simulations process of different GW samples follows the procedure presented in refs. [497,502], based on the redshift distributions of unlensed and lensed double compact objects (DCO) from the conservative SFR function [466,503,504]. For each specific GW event, the uncertainties of different observables (time delays, lens modeling, the line of sight contamination, etc.)…”
Section: -13mentioning
confidence: 99%